The Hatschekiidae (Copepoda: Siphonostomatoida) of Moreton Bay, Queensland, Australia, with a key to species reported from Australian waters - Boxshall, Geoffrey A.; Bernot, James P. (Zootaxa, 2025)
Eleven species of Hatschekia are recorded from the marine actinopterygian fishes of Moreton Bay, Queensland. Three of these are new to science: H. amyemmarum sp. nov. from Arothron hispidus (Linnaeus, 1758) and Arothron nigropunctatus (Bloch & Schneider, 1801), H. cribbi sp. nov. from Abudefduf bengalensis (Bloch, 1787), and H. cutmorei sp. nov. from Glaucosoma scapulare Ramsay, 1881. Of these three species, only H. cribbi sp. nov. is known from both sexes. Another seven species are new to Australia: H. aigoi Izawa, 2016 from Siganus fuscescens (Houttuyn, 1782), H. bifurcata Yamaguti & Yamasu, 1959 from Diploprion bifasciatum Cuvier, 1828, H. cernae Goggio, 1905 from Epinephelus coioides (Hamilton, 1822), H. geniculata Uyeno & Nagasawa, 2013 from Arothron nigropunctatus (a new host record), H. pholas (Wilson, 1906) from Arothron stellatus (Anonymous, 1798), H. quadrata Hewitt, 1969 from Tragulichthys jaculiferus (Cuvier, 1818) and Dicotylichthys punctulatus Kaup, 1885 (the latter being a new host record), and H. shari Uyeno & Ali, 2013 from Lethrinus nebulosus (Forsskål, 1775) and L. laticaudis Alleyne & MacLeay, 1877 in Moreton Bay (with the latter being a new host record). This species also occurred on L. nebulosus in New Caledonia. In addition, H. difficilis Kabata, 1991 is reported for the second time from its type host, Scarus ghobban Forsskål, 1775. Males are described for the first time for H. quadrata and H. pholas, and the importance of the males in taxonomy and in analysing relationships is discussed. Hatschekia flatti Uma Devi & Shyamasundari, 1980 is recognised as a junior subjective synonym of the distinctive H. cernae.